Investigation and modelling of the pyrolysis kinetics of industrial biomass wastes. (1st October 2022) - Bieniek, Artur; Reinmöller, Markus; Küster, Felix; Gräbner, Martin; Jerzak, Wojciech; Magdziarz, Aneta
Abstract: Pyrolysis of the waste organic fraction is expected to be a central element to meet the primary energy demand in future: it increases the impact of renewable energy sources on the power generation sector and allows the amount of waste to be reduced, putting an end to landfills. In the present study, kinetic studies on the pyrolysis of biomass wastes are carried out. Two kinds of industrial organic waste are investigated: brewery spent grain (BSG) and medium-density fiberboard (MDF). The main target of this work is to provide a global equation for the one-step pyrolysis reaction of the investigated materials in an argon atmosphere using isoconversional methods. The conducted analysis allowed to estimate the activation energy as 225.4–253.6 kJ/mol for BSG and 197.9–216.7 kJ/mol for MDF. For both materials nth order reaction was proposed with reaction order of 7.69–8.70 for BSG and 6.32–6.55 for MDF. The developed equation allowed to simulate the theoretical curves of thermal conversion. These curves indicated the highest conversion at the temperature of the degradation of dominant component, which was experimentally verified. By this method, a one-step kinetic model is derived, which can be applied for the reaction kinetics in the CFD modelling of, e.g., pyrolysis and gasification processes. Graphical abstract: Image 1 Highlights: The kinetic triplets of BSG and MDF pyrolysis in argon were determined. Friedman, Flyn-Wall-Ozawa, and Kissinger-Akahira-Sunose methods were compared. The calculated reaction order of pyrolysis of BSG and MDF was 8.70 and 6.55, respectively. The single-step reaction of BSG and MDF pyrolysis was simulated using the Runge-Kutta method. The modelled pyrolysis curves were successfully verified via experimental results.